2018
DOI: 10.3389/fimmu.2018.02929
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Transcriptional Regulation in the Induction, Maintenance, Heterogeneity, and Recall-Response of Effector and Memory Th2 Cells

Abstract: Antigen-primed T cells respond to restimulation much faster than naïve T cells and form the cellular basis of immunological memory. The formation of memory Th2 cells starts when naïve CD4 T cells are transformed into effector Th2 cells and is completed after antigen clearance and a long-term resting phase accompanied by epigenetic changes in the Th2 signature genes. Memory Th2 cells maintain their functions and acquired heterogeneity through epigenetic machinery, on which the recall-response of memory Th2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 110 publications
1
20
0
Order By: Relevance
“…Allergen-specific Th2 cells orchestrate allergic airway inflammation by producing type 2 cytokines, including IL-4, IL-5, and IL-13, which drive eosinophilic inflammation, mucus metaplasia, and airway hyperresponsiveness ( Lambrecht et al, 2019 ; Walker and McKenzie, 2018 ). In addition, Th2 cells can give rise to long-lived memory Th2 cells that maintain allergen-specific immunity ( Hondowicz et al, 2016 ; Onodera et al, 2018 ). Consequently, memory Th2 cells represent an attractive therapeutic target in allergic asthma, but our knowledge of memory Th2 biology in vivo remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Allergen-specific Th2 cells orchestrate allergic airway inflammation by producing type 2 cytokines, including IL-4, IL-5, and IL-13, which drive eosinophilic inflammation, mucus metaplasia, and airway hyperresponsiveness ( Lambrecht et al, 2019 ; Walker and McKenzie, 2018 ). In addition, Th2 cells can give rise to long-lived memory Th2 cells that maintain allergen-specific immunity ( Hondowicz et al, 2016 ; Onodera et al, 2018 ). Consequently, memory Th2 cells represent an attractive therapeutic target in allergic asthma, but our knowledge of memory Th2 biology in vivo remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Antigen-specific Th2 cells cause allergic diseases, such as asthma, rhinitis, and atopic dermatitis, by producing Th2 cytokines (IL-4, IL-5, and IL-13). Antigen-specific Th2 cells generally exist as memory Th2 cells in vivo , and become activated and mediate allergic inflammation immediately after exposure to specific antigens [ 19 21 ]. We previously reported the involvement of antigen-specific Th2 cells in rhinitis, using a mouse model, and found that the nasal activation of antigen-specific Th2 cells induced rhinitis symptoms even in the absence of IgE, mast cells, and basophils [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, natural substances, such as polyphenols, that can interfere with phase I and/or II enzymes and/or with enteric P-glycoprotein enhance its plasma levels in rats ∼6-fold (73). Finally, among the three compounds tested in our investigation, cannabidiol is the only ingredient that has been studied in dogs, where its detected oral bioavailability ranged from 13 to 19% of the administered dose (74,75). Therefore, despite our study being performed in vitro, these previously reported findings suggest that our results could be considered valid with respect to a nutraceutical approach to treating canine AD.…”
Section: Discussionmentioning
confidence: 81%